2014
DOI: 10.1037/a0037229
|View full text |Cite
|
Sign up to set email alerts
|

Response monitoring and adjustment: Differential relations with psychopathic traits.

Abstract: Studies on the relation between psychopathy and cognitive functioning often show mixed results, partially because different factors of psychopathy have not been considered fully. Based on previous research, we predicted divergent results based on a two-factor model of psychopathy (interpersonal-affective traits and impulsive-antisocial traits). Specifically, we predicted that the unique variance of interpersonal-affective traits would be related to increased monitoring (i.e., error-related negativity) and adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 107 publications
4
17
0
2
Order By: Relevance
“…Also, we did not observe an association between PES and psychopathy, consistent with previous incarcerated adult male samples (Munro et al, 2007;Brazil et al, 2009;. Recently, PES has been associated with self-reported psychopathic traits in community samples comprised of males and females (Bresin et al, 2014). This raises the possibility that methodological differences may account for the discrepant findings, including differences in measurement of psychopathy (self-report vs expert-rater devices) and clinical levels of psychopathy (community samples vs forensic samples).…”
Section: Discussionsupporting
confidence: 66%
“…Also, we did not observe an association between PES and psychopathy, consistent with previous incarcerated adult male samples (Munro et al, 2007;Brazil et al, 2009;. Recently, PES has been associated with self-reported psychopathic traits in community samples comprised of males and females (Bresin et al, 2014). This raises the possibility that methodological differences may account for the discrepant findings, including differences in measurement of psychopathy (self-report vs expert-rater devices) and clinical levels of psychopathy (community samples vs forensic samples).…”
Section: Discussionsupporting
confidence: 66%
“…Reduced ERN/Ne amplitudes have been measured in individuals with elevated psychopathic traits (Dikman & Allen, 2000; Heritage & Benning, 2012). Recently, increased ERN/Ne has been identified in a community sample with a criminal history and elevated psychopathic traits as measured with the Psychopathy Checklist: Screening Version (PCL-SV; Bresin, Finy, Sprague, & Verona, 2014). Other studies have not identified ERN/Ne differences related to psychopathic traits in standard tasks (Brazil et al, 2009; Brazil et al, 2011; Munro et al, 2007) but have in an affective flanker (Munro, et al, 2007).…”
mentioning
confidence: 99%
“…De plus, des études démontrent que ces traits peuvent également être adaptatifs dans certains contextes, protégeant l'individu de troubles émotionnels et contribuant à leur influence sociale (Lilienfeld et al, 2012 ;Miller & Lynam, 2012). Dans le domaine de la cognition, nous avons observé que les traits reliés au Facteur 1 étaient associés à un meilleur fonctionnement exécutif (Sellbom & Verona, 2007), à une surveillance appropriée de la réponse et à l'ajustement comportemental (Bresin, Finy, Sprague & Verona, 2014). Ces résultats pourraient suggérer que dans le cas où ces individus se tournent vers le crime, ils présenteraient une tendance à arnaquer autrui, à s'engager dans certaines activités criminelles organisées et seraient plus difficiles à appréhender.…”
Section: Resultsunclassified